Pengaruh Variasi Lama Waktu Perebusan terhadap Karakteristik Fisikokimia Tepung Kluwih Termodifikasi dengan Metode Perebusan-Pendinginan - Lukman Azis; Azzahra Putri Diandra; Lumina Astrid Utami; Hamidatun Hamidatun (Universitas Al Azhar Indonesia, 2026)
Kluwih (Artocarpus camansi) is an underutilized starch-rich crop with promising potential for development as a functional food ingredient through starch modification. This study aimed to analyse the physicochemical properties of modified kluwih flour produced via a boiling–cooling process. A completely randomized design (CRD) with a single factor namely boiling time (0, 5, 10, and 15 min) was applied, followed by cooling and drying. The evaluated parameters included proximate composition (moisture, ash, fat, protein, and carbohydrate by difference), amylose and amylopectin contents, resistant starch, and color characteristics (L, a*, b*). Boiling time significantly influenced most physicochemical attributes (p < 0.05). Prolonged boiling increased moisture, carbohydrate, and resistant starch contents, while decreasing fat, protein, ash, and amylose levels. The highest resistant starch content (16.74 g/100 g) was achieved at 15 min of boiling. These changes are attributed to starch gelatinization during heating and subsequent retrogradation upon cooling. Furthermore, boiling duration significantly affected flour brightness. In conclusion, the boiling–cooling method effectively modified the physicochemical characteristics of kluwih flour. A 15-min boiling treatment optimized resistant starch formation, highlighting its potential for functional food applications.Keywords - Boiling–Cooling, Kluwih, Modified Flour, Proximate Composition, Resistant Starch.